Effects of Arctiin on Streptozotocin-Induced Diabetic Retinopathy in Sprague-Dawley Rats - Lu, Lai-chun; Zhou, Wei; Li, Zhuo-heng; Yu, Cai-ping; Li, Chen-wen; Luo, Ming-he; Xie, Hong (Planta Medica, 2012)
Diabetic retinopathy is one of the most common and severe complications of diabetes mellitus. Arctiin, a bioactive compound isolated from the dry seeds of Arctium lappa L., has been reported to have antidiabetic activity. In this study, we investigated the effect of arctiin on the serum glucose and HBA1c levels, the blood viscosity, and VEGF expression in the retinal tissues of rats with diabetic retinopathy. We first extracted arctiin from Fructus Arctii and then investigated its chemopreventive effect on streptozotocin-induced diabetic retinopathy in male Sprague-Dawley rats. After the induction of diabetes using streptozotocin (30 mg/kg, i. p.), the rats were randomly divided into five groups (n = 20 per group) and treated with intragastric doses of 30, 90, or 270 mg/kg/d wt of arctiin, 100 mg/kg/d wt of calcium dobesilate, or 0.5 % CMC-Na. Twenty nondiabetic sham-treated rats were treated with 0.5 % CMC-Na. The occurrence of diabetic retinopathy did not differ dramatically among the groups. However, at week 16, the glycosylated haemoglobin (HBA1c) level was significantly decreased in all of the arctiin-treated groups when compared with the control group, and the serum glucose level was also decreased in the rats treated with the highest dose of arctiin. In addition, treatment with arctiin ameliorated retinal oedema, detachment of the retina, and VEGF expression in the retina, as detected using histological and immunochemical examinations. Finally, arctiin increased the viability of retinal microvascular endothelial cells in vitro. Together, these findings demonstrate that arctiin decreases the severity of diabetic complications, demonstrating the importance of this compound as an inhibitor of diabetic retinopathy.
Keywords: arctiin; diabetic retinopathy; HBA1c; retina; retinal microvascular endothelial cell